Traditional Mongolian medicine Eerdun Wurile improves stroke recovery through regulation of gene expression in rat brain. (10th August 2018) - Gaowa, Saren; Bao, Narisi; Da, Man; Qiburi, Qiburi; Ganbold, Tsogzolmaa; Chen, Lu; Altangerel, Altanzul; Temuqile, Temuqile; Baigude, Huricha
Abstract: Ethnopharmacological relevance: Eerdun Wurile (EW) is one of the key Mongolian medicines for treatment of neurological and cardiological disorders. EW is ranked most regularly used Mongolian medicine in clinic. Components of EW which mainly originate from natural products are well defined and are unique to Mongolian medicine. Aim of the study: Although the recipe of EW contains known neuroactive chemicals originated from plants, its mechanism of action has never been elucidated at molecular level. The objective of the present study is to explore the mechanism of neuroregenerative activity of EW by focusing on the regulation of gene expression in the brain of rat model of stroke. Materials and methods: Rat middle cerebral artery occlusion (MCAO) models were treated with EW for 15 days. Then, total RNAs from the cerebral cortex of rat MCAO models treated with either EW or control (saline) were extracted and analyzed by transcriptome sequencing. Differentially expressed genes were analyzed for their functions during the recovery of ischemic stroke. The expression level of significantly differentially expressed genes such as growth factors, microglia markers and secretive enzymes in the lesion was further validated by RT-qPCR and immunohistochemistry. Results: Previously identified neuroactive compounds, such as geniposide (Yu et al., 2009), myristicin (Shin et al., 1988), costunolide (Okugawa et al., 1996), toosendanin (Shi and Chen, 1999) were detected in EW formulation. Bederson scale indicated that the treatment of rat MCAO models with EW showed significantly lowered neurological deficits (p < 0.01). The regional cerebral blood circulation was also remarkably higher in rat MCAO models treated with EW compared to the control group. A total of 186 genes were upregulated in the lesion of rat MCAO models treated with EW compared to control group. Among them, growth factors such as Igf1 (p < 0.05), Igf2 (p < 0.01), Grn (p < 0.01) were significantly upregulated in brain after treatment of rat MCAO models with EW. Meanwhile, greatly enhanced expression of microglia markers, as well as complementary components and secretive proteases were also detected. Conclusion: Our data collectively indicated that EW enhances expression of growth factors including Igf1 and Igf2 in neurons and microglia, and may stimulate microglia polarization in the brain. The consequences of such activity include stimulation of neuron growth, hydrolysis and clearance of cell debris at the lesion, as well as the angiogenesis. Graphical abstract: